AKIBAT HUKUM PENETAPAN TANAH TERLANTAR HAK GUNA BANGUNAN YANG SEMULA DIKUASAI PT TAMAN HARAPAN INDAH: The Legal Consequences of Determining Abandoned Land With Building Use Rights Which Controlled by PT Taman Harapan Indah - Damara, Fenny; Pandamdari, Endang (AMICUS CURIAE, 2024)
Currently, many individuals own land but do not utilize it effectively. Neglecting land is an unwise action. This research focuses on the procedure of determining abandoned land previously owned by PT Taman Harapan Indah with the Right to Build (Hak Guna Bangunan - HGB) in accordance with prevailing regulations, along with the legal consequences of such determination based on the Supreme Court Decision Number 565/K/TUN/2020, which was accepted by the rights holder. To address this issue, the research is conducted using a normative legal method, relying on secondary data with qualitative analysis. The conclusions drawn in this research are based on a deductive approach. The research findings indicate that the determination of abandoned land by PT Taman Harapan Indah was carried out based on Government Regulation (PP) 11/2010, with the determination made through Decree (Surat Keputusan - SK) Number 1/PTT-HGB/KEM-ATR/BPN/IV/2019. The legal impact received by PT Taman Harapan Indah, according to the Supreme Court Decision Number 565/K/TUN/2020, includes the revocation of its land rights, the termination of the legal relationship between the landowner and the land, accompanied by an affirmation that the land is now under state control.